Analysis of Structure, Morphology, Magnetic Properties, and Microwave Absorption of Lanthanum Orthoferrite (LaFeO3) - Naibaho, Marzuki; Widakdo, Januar; Kurniawan, Budhy; Nehan, Phahul Zhemas Zul; Vitayaya, Okvarahireka; Novita; Ramlan; Adi, Wisnu Ari; Ginting, Masno (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
LaFeO3 has been prepared using the solid-state reaction method with High Energy Milling (HEM). The preparation of LaFeO3 was carried out using stoichiometric calculations. Based on the XRD measurement results, single-phase LaFeO3 with an orthorhombic crystal structure was obtained. From the SEM results, the morphology of LaFeO3 is uniform, and the EDS results show the weight percentage of La, Fe, and O elements are 49.74, 21.08, and 29.18 wt%, respectively. VSM LaFeO3 results show magnetic saturation, remanence, and coercivity are 0.24 emu/g, 0.02 emu/g, and 853.38 Oe, respectively, and the absorption of LaFeO3 is -7.40 dB at a frequency of 6.02 GHz with a LaFeO3 sample thickness of 1.5mm.